Thermospheric Neutral Density Variation During the “SpaceX” Storm: Implications From Physics‐Based Whole Geospace Modeling - Dong Lin; Wenbin Wang; Katherine Garcia‐Sage; Jia Yue; Viacheslav Merkin; Joseph M. McInerney; Kevin Pham; Kareem Sorathia (Space Weather)
Abstract The Starlink satellites launched on 3 February 2022 were lost before they fully arrived in their designated orbits. The loss was attributed to two moderate geomagnetic storms that occurred consecutively on 3–4 February. We investigate the thermospheric neutral mass density variation during these storms with the Multiscale Atmosphere‐Geospace Environment (MAGE) model, a first‐principles, fully coupled geospace model. Simulated neutral density enhancements are validated by Swarm satellite measurements at the altitude of 400–500 km. Comparison with standalone TIEGCM and empirical NRLMSIS 2.0 and DTM‐2013 models suggests better performance by MAGE in predicting the maximum density enhancement and resolving the gradual recovery process. Along the Starlink satellite orbit in the middle thermosphere (∼200 km altitude), MAGE predicts up to 150% density enhancement near the second storm peak while standalone TIEGCM, NRLMSIS 2.0, and DTM‐2013 suggest only ∼50% increase. MAGE also suggests altitudinal, longitudinal, and latitudinal variability of storm‐time percentage density enhancement due to height dependent Joule heating deposition per unit mass, thermospheric circulation changes, and traveling atmospheric disturbances. This study demonstrates that a moderate storm can cause substantial density enhancement in the middle thermosphere. Thermospheric mass density strongly depends on the strength, timing, and location of high‐latitude energy input, which cannot be fully reproduced with empirical models. A physics‐based, fully coupled geospace model that can accurately resolve the high‐latitude energy input and its variability is critical to modeling the dynamic response of thermospheric neutral density during storm time.